Droplet Digital PCR for Estimating Absolute Abundances of Widespread Pelagibacter Viruses - Martinez-Hernandez, Francisco; Garcia-Heredia, Inmaculada; Lluesma Gomez, Monica; Maestre-Carballa, Lucia; Martínez Martínez, Joaquín; Martinez-Garcia, Manuel (Frontiers in Microbiology, 2019)
Absolute abundances of prokaryotes are typically determined by FISH. Due to the lack of a universal conserved gene among all viruses, metagenomic fragment recruitment is commonly used to estimate the relative viral abundance. However, the paucity of absolute virus abundance data hinders our ability to fully understand how viruses drive global microbial populations. The cosmopolitan marine Pelagibacter ubique is host for the highly widespread HTVC010P pelagiphage isolate and the extremely abundant uncultured virus vSAG 37-F6 recently discovered by single-virus genomics. Here we applied droplet digital PCR (ddPCR) to calculate the absolute abundance of these pelagiphage genotypes in the Mediterranean Sea and the Gulf of Maine. Abundances were between 270–1,740 virus mL-1 and 950–1,610 virus mL-1 for vSAG 37-F6 and HTVC010P, respectively. Illumina PCR-amplicon sequencing corroborated the absence of ddPCR non-specific amplifications for vSAG 37-F6, but showed an overestimation of 6% for HTVC010P from off-targets, genetically unrelated viruses. Absolute abundances of both pelagiphages, two of the most abundance marine viruses, suggest a large viral pelagiphage diversity in marine environments, and show the efficiency of ddPCR to disentangle the marine viral structure. Results also highlight the need for a standardized workflow to obtain accurate quantification that allows cross data comparison